Climbing Mont Blanc (4808 m a.s.l.): What Are the Risks in the Grand Couloir Du Goûter and On the North Face of Mont Blanc Du Tacul? - Ludovic Ravanel; Jacques Mourey; Lorig Tamian; Sébastien Ibanez; Didier Hantz; Pascal Lacroix; Pierre-Allain Duvillard (Revue de Géographie Alpine)
Mountaineering is a sport highly dependent on the conditions of the physical environments in which it takes place. As a result, mountaineers have to deal with major glacial and periglacial hazards, such as those affecting the two main routes used to climb Mont Blanc (4808 m a.s.l.; Western European Alps): rockfalls in the Grand Couloir du Goûter on the Voie Royale and serac falls on the NNW slope of Mont Blanc du Tacul on the Trois Monts route. Hazards in these two sectors and the number of climbers were measured using a multi-sensor system and automatic photographic acquisition, respectively. On the first site, which has a very high accident rate with an average of 3.7 deaths per year, 17,768 passages were recorded during the summer of 2019 and 2,648 seismic signals were classified as rockfalls affecting the Grand Couloir. The average risk of death associated with these rockfalls, the frequency of which depends on temperatures and the presence of liquid water in the ground, is estimated at 1.7 × 10-4. At Tacul, where an average of 0.6 deaths occur each year, 6,770 passages were recorded during the summer of 2017, as well as 31 serac falls unrelated to temperatures. The risk of death is 8.3 × 10-5. The risk is also quantified for each track made on the glacier. The results obtained makes it possible to specify the risks experienced by climbers and to promote risk reduction strategies.